Recent advances in diverse nanosystems for nitric oxide delivery in cancer therapy - Dan Gao; Sajid Asghar; Rongfeng Hu; Su Chen; Ruixin Niu; Jia Liu; Zhipeng Chen; Yanyu Xiao (Elsevier, 2023)
Gas therapy has been proven to be a promising and advantageous treatment option for cancers. Studies have shown that nitric oxide (NO) is one of the smallest structurally significant gas molecules with great potential to suppress cancer. However, there is controversy and concern about its use as it exhibits the opposite physiological effects based on its levels in the tumor. Therefore, the anti-cancer mechanism of NO is the key to cancer treatment, and rationally designed NO delivery systems are crucial to the success of NO biomedical applications. This review summarizes the endogenous production of NO, its physiological mechanisms of action, the application of NO in cancer treatment, and nano-delivery systems for delivering NO donors. Moreover, it briefly reviews challenges in delivering NO from different nanoparticles and the issues associated with its combination treatment strategies. The advantages and challenges of various NO delivery platforms are recapitulated for possible transformation into clinical applications.